2017
DOI: 10.1080/03009734.2017.1294635
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing atelectasis formation during general anaesthesia—oxygen washout is a non-essential supplement to PEEP

Abstract: BackgroundFollowing preoxygenation and induction of anaesthesia, most patients develop atelectasis. We hypothesized that an immediate restoration to a low oxygen level in the alveoli would prevent atelectasis formation and improve oxygenation during the ensuing anaesthesia.MethodsWe randomly assigned 24 patients to either a control group (n = 12) or an intervention group (n = 12) receiving an oxygen washout procedure directly after intubation. Both groups were, depending on body mass index, ventilated with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Recently, two studies have demonstrated that a PEEP level of 6 to 7 cmH 2 O as a single intervention in nonobese patients results in an ‘open lung’ with minimal atelectasis, as investigated by computed tomography immediately before emergence from anaesthesia. 32,33 Extrapolating from these two studies and the current study, the following implication might evolve: If pre-oxygenation starts, using first a CPAP of 6 to 7 cmH 2 O and then a PEEP of the same magnitude during induction of anaesthesia, this should both give the respiratory advantages and definitely be safe in healthy, fasting patients, such as in this study, as long as PIP is no higher than 15 cmH 2 O. This is assuming that the risk for gastric insufflation with lower PEEP at equal PIP per se is not higher than with PEEP of 10 cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies have demonstrated that a PEEP level of 6 to 7 cmH 2 O as a single intervention in nonobese patients results in an ‘open lung’ with minimal atelectasis, as investigated by computed tomography immediately before emergence from anaesthesia. 32,33 Extrapolating from these two studies and the current study, the following implication might evolve: If pre-oxygenation starts, using first a CPAP of 6 to 7 cmH 2 O and then a PEEP of the same magnitude during induction of anaesthesia, this should both give the respiratory advantages and definitely be safe in healthy, fasting patients, such as in this study, as long as PIP is no higher than 15 cmH 2 O. This is assuming that the risk for gastric insufflation with lower PEEP at equal PIP per se is not higher than with PEEP of 10 cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting FiO 2 was 33%, although a FiO 2 of 42% is reported by the manufacturer (In Case of Anaesthesia, n.d.). As high FiO 2 is associated with increased shunt fraction in other species, the lower FiO 2 provided by this ventilator may have been beneficial in preventing further atelectasis (De Monte et al 2013;Osbertg et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, trained personnel and a functioning pre-and a post-anesthesia care unit are mandatory. CPAP ventilation within the scope of regular preoxygenation and immediately after extubation is feasible in any case without further technical effort, but might not be this effective (12). Especially for high-risk patients (FEV1 <70%) and for patients requiring postoperative intensive care, continued CPAP ventilation is highly recommended.…”
Section: Editorialmentioning
confidence: 99%